Diagnostic Evaluation and Management of Chronic Thromboembolic Pulmonary Hypertension: A Clinical Practice Guideline - Sanjay Mehta; Doug Helmersen; Steeve Provencher; Naushad Hirani; Fraser D Rubens; Marc De Perrot; Mark Blostein; Kim Boutet; George Chandy; Carole Dennie; John Granton; Paul Hernandez; et al. (Canadian Respiratory Journal)
BACKGROUND: Pulmonary embolism is a common condition. Some patients subsequently develop chronic thromboembolic pulmonary hypertension (CTEPH). Many care gaps exist in the diagnosis and management of CTEPH patients including lack of awareness, incomplete diagnostic assessment, and inconsistent use of surgical and medical therapies.